INTERFERENSI MORFOLOGI DAN SINTAKSIS BAHASA INDONESIA DALAM BERBICARA BAHASA ARAB KOMUNITAS AL-KINDY UIN MALANG - Yuslizar, Firsa Afra; Arifa, Zakiyah (Lisanul Arab: Journal of Arabic Learning and Teaching, 2021)
This research is based on the problem of morphological and syntactical first language interference which is often overlooked in second language learning. Interference problems result in misunderstanding the meaning of words or sentences spoken by students towards the second language used. This study attempts to analyze the Indonesian morphological and syntactical interference in speaking Arabic of Al-Kindy community UIN Malang, explaining the factors and implications of interference in learning speaking Arabic. This research method uses a descriptive qualitative approach, and the data are collected through observation by analyzing subject audio documentation data (listening technique- note-taking technique) and interviews. The results showed that members of the al-Kindy community experienced Indonesian morphological interference in word formation, merging/compounding, repetition/reduplication. Meanwhile, Indonesian syntactical interference occurs in: adding sentence elements, errors (sentence elements, sentence location, phrase formation), and missing sentence elements. The factors of the interference are bilingualism, vocabulary mastery, motivation, and psychology of speakers towards the Arabic used. Interference has implications for barriers and challenges in Arabic language learning. The barriers are in the intensity of language interference phenomena, so the language quality is stagnant, and the challenges are to make interference phenomena as motivation for learners to evaluate the language learning process better